Neoadjuvant Long-Course Chemoradiotherapy for Rectal Cancer: Does Time to Surgery Matter? - Panagiotopoulou, Ioanna G. (Int Surg, 2015)
The objective of this paper was to evaluate whether delaying surgery following long-course chemoradiotherapy for rectal cancer correlates with pathologic complete response. Pre-operative chemoradiotherapy (CRT) is standard practice in the UK for the management of locally advanced rectal cancer. Optimal timing of surgery following CRT is still not clearly defined. All patients with a diagnosis of rectal cancer who had undergone long-course CRT prior to surgery between January 2008 and December 2011 were included. Statistical analysis was performed using Stata 11. Fifty-nine patients received long-course CRT prior to surgery in the selected period. Twenty-seven percent (16/59) of patients showed a complete histopathologic response and 59.3% (35/59) of patients had tumor down-staging from radiologically-assessed node positive to histologically-proven node negative disease. There was no statistically significant delay to surgery after completion of CRT in the 16 patients with complete response (CR) compared with the rest of the group [IR: incomplete response; CR group median: 74.5 days (IQR: 70–87.5) and IR group median: 72 days (IQR: 57–83), P = 0.470]. Although no statistically significant predictors of either complete response or tumor nodal status down-staging were identified in logistic regression analyses, a trend toward complete response was seen with longer delay to surgery following completion of long-course CRT.